VIDEOCONFERENCING FOR SPEAKING ASSESSMENT MEDIUM: ALTERNATIVE OR DRAWBACK? - Muhamad Nova (Premise: Journal of English Education and Applied Linguistics, 2020)
The urgency of technology integration has arisen due to the current pandemic break. With a sudden shift from conventional learning to virtual learning, less proper preparation on utilizing the technology integration may occur. The present study aimed at unraveling the perception and obstacles faced during the implementation of videoconferencing as a speaking assessment medium. By applying qualitative research with a snapshot case study design in a vocational education institution, this study gained the data through questionnaires, focus group discussion, and an interview. As a result, the majority of the students perceived negatively toward the implementation of videoconferencing as a speaking assessment medium. These negative reactions occurred due to the nervousness and anxiety along the online speaking assessment process. Moreover, the obstacles faced, such as bad internet connection, technical problems, and surrounding disturbance, also contributed an impact on students’ language production and the sound heard by the students during the online speaking assessment. From the results of the present study, the application of videoconferencing as a medium in assessing students’ speaking ability needs to be reappraised to preview its function whether it can be used as an alternative way or it contributes a drawback effect during the assessment process.